ChemInform Abstract: Heterogeneous Light‐Mediated Reductive Dehalogenations and Cyclizations Utilizing Platinum Nanoparticles on Titania (PtNP@TiO2). Issue 11 (March 2015) - McTiernan, Christopher D.; Pitre, Spencer P.; Ismaili, Hossein; Scaiano, Juan C.
Abstract A highly reductive photoredox system based on heterogeneous platinum nanoparticles on titania as catalyst is described to allow hydrodehalogenation of iodoarenes, hydrodehalogenation and cyclization of a variety of allyl and propargyl tethered iodoethyl compounds, and the cyclization of bisenones of type (XVII).